2009
DOI: 10.1093/nar/gkp594
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional combinatorial screening and the RNA Privileged Space Predictor program efficiently identify aminoglycoside–RNA hairpin loop interactions

Abstract: Herein, we report the identification of RNA hairpin loops that bind derivatives of kanamycin A, tobramycin, neamine, and neomycin B via two-dimensional combinatorial screening, a method that screens chemical and RNA spaces simultaneously. An arrayed aminoglycoside library was probed for binding to a 6-nucleotide RNA hairpin loop library (4096 members). Members of the loop library that bound each aminoglycoside were excised from the array, amplified and sequenced. Sequences were analyzed with our newly develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 61 publications
(95 reference statements)
1
49
0
Order By: Relevance
“…For example, studies by Wong and co-workers showed that several aminoglycosides have only limited specificity for binding a variety of RNAs that mimic the bacterial rRNA A-site (39). In this current and other previously reported 2DCS studies (16-18, 21), specific RNA structures that bind aminoglycosides have been identified using only a single round of selection. With the bacterial rRNA A-site-like library, overlap of statistically significant trends in the 2DCS selections have helped to identify the RNA motifs that prefer to specifically bind an aminoglycoside (Figure 3).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, studies by Wong and co-workers showed that several aminoglycosides have only limited specificity for binding a variety of RNAs that mimic the bacterial rRNA A-site (39). In this current and other previously reported 2DCS studies (16-18, 21), specific RNA structures that bind aminoglycosides have been identified using only a single round of selection. With the bacterial rRNA A-site-like library, overlap of statistically significant trends in the 2DCS selections have helped to identify the RNA motifs that prefer to specifically bind an aminoglycoside (Figure 3).…”
Section: Resultsmentioning
confidence: 85%
“…The structures were then analyzed computationally for commonalities using the RNA P rivileged S pace P redictor (RNA-PSP) Program, version 1.1 (18). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,23 This approach, Two-Dimensional Combinatorial Screening (2DCS), coupled with identifying statistically significant, unique features in the selected RNAs, 11,12 afforded high affinity and selective interactions. This information was then used in drug discovery efforts to target triplet-repeating and tetra-repeating RNA transcripts that cause disease.…”
Section: Resultsmentioning
confidence: 99%
“…The authors applied a particularly clever screening methodology called 2D combinatorial screening (2DCS) [65][66][67]. In 2DCS, a small-molecules library is conjugated onto an agarose microarray surface.…”
Section: Focused Screening Approachmentioning
confidence: 99%